Development of a mouse iron overload-induced liver injury model and evaluation of the beneficial effects of placenta extract on iron metabolism. Issue 5 (May 2019) - Yamauchi, Akihiro; Kamiyoshi, Akiko; Sakurai, Takayuki; Miyazaki, Hiroyuki; Hirano, Eiichi; Lim, Hong-Seok; Kaku, Taiichi; Shindo, Takayuki
Abstract: Hepatic iron deposition is seen in cases of chronic hepatitis and cirrhosis, and is a hallmark of a poorer prognosis. Iron deposition is also found in non-alcoholic steatohepatitis (NASH) patients. We have now developed a mouse model of NASH with hepatic iron deposition by combining a methione- and choline-deficient (MCD) diet with an iron-overload diet. Using this model, we evaluated the effects of human placenta extract (HPE), which has been shown to ameliorate the pathology of NASH. Four-week-old male C57BL/6 mice were fed the MCD diet with 2% iron for 12 weeks. In liver sections, iron deposition was first detected around the portal vein after 1 week. From there it spread throughout the parenchyma. Biliary iron concentrations were continuously elevated throughout the entire 12-week diet. As a compensatory response, the diet caused elevation of serum hepcidin, which accelerates excretion of iron from the body. Accumulation of F4/80-positive macrophages was detected within the sinusoids from the first week onward, and real-time PCR analysis revealed elevated hepatic expression of genes related inflammation and oxidative stress. In the model mice, HPE treatment led to a marked reduction of hepatic iron deposition with a corresponding increase in biliary iron excretion. Macrophage accumulation was much reduced by HPE treatment, as was the serum oxidation-reduction potential, an index of oxidative stress. These data indicate that by suppressing inflammation, oxidative stress and iron deposition, and enhancing iron excretion, HPE effectively ameliorates iron overload-induced liver injury. HPE administration may thus be an effective strategy for treating NASH.